Confronting the representative consumer with household-size heterogeneity - Christos Koulovatianos; Carsten Schröder; Ulrich Schmidt (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
Much analysis in macroeconomics empirically addresses economy-wide incentives behind consumer/investment choices by using insights from the way a single representative household would behave. Heterogeneity at the micro level can jeopardize attempts to back up the representative consumer construct with microfoundations. One complex aspect of micro-level heterogeneity is household size, as individuals living in multi-member households have the potential to share goods within the household, benefiting from household-size economies. Theoretically, we show that validating the role of a representative consumer would require that the way individuals benefit from intra-household sharing is strictly aligned across the rich and the poor: once expenditures for subsistence needs are subtracted from disposable household income, household-size economies the remainder (discretionary) household incomes entail must be the same across the rich and the poor. We have designed a survey method that allows the testing of this stringent property of intra-household sharing and find that it holds.
Keywords: C42; E21; D12; E01; D11; D91; D31; I32; 330; Linear Aggregation; Equivalent; xpenditures; SurveyMethod; Household-Size Economies; Gesamtwirtschaftlicher Konsum; Konsumtheorie; Haushaltsökonomik; Verbraucherausgaben; Befragung; Theorie